Welfare and the depth of informality: Evidence from five African countries - Eva-Maria Egger; Cecilia Poggi; Hector Gutierrez Rufrancos (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
This study explores the relationship between household poverty and depth of informality by proposing a new measure of informality at the household level. It is defined as the share of activities (hours worked or income earned) without social insurance for wage workers in the household. We apply cross-sectional regressions to five urban sub-Saharan African countries, showing that a household head informality dummy obscures a non-linear relationship between the depth of household informality and welfare outcomes. In some countries, a small share of income from formal jobs is associated with at least the same welfare as a fully formal portfolio. By assessing transitions between household portfolios with panel data for urban Nigeria, we also show that most welfare differences are explained by selection and that movements in and out of formality cannot sufficiently change welfare trajectories. The results call for better inclusion of informal profiles to social insurance programmes.
Keywords: H55; I31; J46; J88; 330; informality; measurement; poverty; social protection; sub-Saharan Africa